Business Development Strategies Formulation based on Business Model Canvas, SWOT Analysis, And AHP - Yulia Yumiza; V. Reza Bayu Kurniawa; Dian Tiara Rezalti (LPPM Universitas Buddhi Dharma, 2024)
Businesses need to continuously improve their comptitive advantage. For top management, formulating a long-term vision is crucial. However, strategic planning representing this long-term vision is often overlooked in SMEs due to their limited competencies and knowledge. Therefore, this study introduces a decision-making model for formulating long-term strategies that should be prioritized in SMEs. The decision-making model is developed using a combination of three methods: business model canvas (BMC), SWOT analysis, and analytic hierarchy process (AHP), and is applied to a bespoke steel house accessories manufacturing service company. The mapping and formulation of business development strategies are completed using BMC and SWOT, followed by determining the strategy priorities based on weights obtained using AHP. The results showed that eight business development strategies representing the company's business model advantages were formulated: warranty (strategy 1), available human resources (strategy 2), on-time delivery (strategy 3), online CRM (strategy 4), discounts (strategy 5), online selling (strategy 6), production cost efficiency (strategy 7), and raw material cost reduction (strategy 8). By using AHP, strategies 7, 8, and 4 are identified as the top three priorities for the company, indicating issues in supply chain management and the use of digital technology in marketing. This study is significant as the developed decision-making model is applied at a strategic level and can be directly utilized by decision-makers in formulating their company’s strategic vision.